Enhancing Medical Image Security Using Hyperchaotic Lorenz and Josephus Traversing Encryption - Rachmawanto, Eko Hari; Pramudya, Elkaf Rahmawan; Pratama, Zudha (Universitas Negeri Semarang, 2024)
Purpose: The present work focuses on developing a methodology to encrypt medical images using combined Hyperchaotic Lorenz systems with Josephus Traversing. This, therefore, forms the basis of the present paper to establish the efficacy of the proposed method against glioma, meningioma, and pituitary kinds of brain tumor images at 256 × 256 and 512 × 512 pixels image sizes. Methods: In this regard, a state-of-the-art encryption technique based on the Hyperchaotic Lorenz systems for Josephus Traversing has been proposed against the medical images of glioma, meningioma, and pituitary tumor datasets obtained from the repository via medical imaging. Result: The different distortion of test outcomes has the MSE value lying between 69.01 and 172.1, while fidelity preservation-PSNR lies between 12.971 and 18.321 dB for different tumor types and sizes of images. The UACI is between 3.625 and 11.34, while the NPCR is always greater than 99% to show very high tamper resistance. This approach is very new in integrating chaos and traversal algorithms for encrypting medical images. Hence, it has a great promising enhancement of security and protection of patient privacy. Novelty: This research contributes a comprehensive investigation based on different metrics that allows exploring not only the efficiency but also strength against decryption techniques for a proposed encryption method. More investigations could be done for further research work in order to enhance the encryption speed, which would improve robustness against advanced decryption techniques in medical image security for digital health applications.